Lay Definitions of Happiness across Nations: The Primacy of Inner Harmony and Relational Connectedness - Delle Fave, Antonella; Brdar, Ingrid; Wissing, Marié P.; Araujo, Ulisses; Castro Solano, Alejandro; Freire, Teresa; Hernández-Pozo, María Del Rocío; Jose, Paul; Martos, Tamás; Nafstad, Hilde E.; Nakamura, Jeanne; Singh, Kamlesh; et al. (Frontiers in Psychology, 2016)
In well-being research the term happiness is often used as synonymous with life satisfaction. However, little is known about lay people’s understanding of happiness. Building on the available literature, this study explored lay definitions of happiness across nations and cultural dimensions, analyzing their components and relationship with participants’ demographic features. Participants were 2799 adults (age range=30-60, 50% women) living in urban areas of Argentina, Brazil, Croatia, Hungary, India, Italy, Mexico, New Zealand, Norway, Portugal, South Africa and United States. They completed the Eudaimonic and Hedonic Happiness Investigation (EHHI), reporting, among other information, their own definition of happiness. Answers comprised definitions referring to a broad range of life domains, covering both the contextual-social sphere and the psychological sphere. Across countries and with little variation by age and gender, inner harmony predominated among psychological definitions, and family and social relationships among contextual definitions. Whereas relationships are widely acknowledged as basic happiness components, inner harmony is substantially neglected. Nevertheless, its cross-national primacy, together with relations, is consistent with the view of an ontological interconnectedness characterizing living systems, shared by several conceptual frameworks across disciplines and cultures. At the methodological level, these findings suggest the potential of a bottom-up, mixed method approach to contextualize psychological dimensions within culture and lay understanding.